Interpretasi kontemporer dengan AI: Prespektif penafsiran Al-Qur’an - Fillah, Maulidia Aisy (Maliki Interdisciplinary Journal, 2026)
Current technological advances have triggered the development of interpretive styles, leading to the emergence of the term contemporary interpretation. This study aims to examine the contemporary interpretive approach through the use of artificial intelligence (AI), which has been widely used by Qur’anic interpreters. One Qur’anic interpreter who uses a contemporary interpretive style is Muhammad Izzat Darwazah (1887-1984), who has had a significant influence on the development of contemporary tafsir studies. This interpreter then uses the tafsir nuzuli method, which emphasizes the importance of interpreting Qur’anic verses based on the chronological order of revelation (tartib al-nuzul). This article will explain that contemporary interpretation of the Qur’an can use AI, but must also be careful and not ignore the classical principles of tafsir science, so that AI can be used to interpret the Qur’an contextually and systematically.